The Effect of Concentration of Stabilizer and Concentration of Yoghurt on the Quality of Belimbing Wuluh Jelly Candy - Indah Novita Sari M.; Terip Karo-Karo; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Jelly candy is candy that made from water or juice with the addition of flavor forming substance, sugar, and gelling agent. The aim of this research was to find the best combination treatment from the concentration of stabilizer with the concentration of yoghurt in producing belimbing wuluh jelly candy with the best characteristic of physcochemical and sensory quality that can be accepted by consumers. Concentration of stabilizer were 2%, 4%, 6%, and 8%. Concentration of yoghurt were 10%, 20%, 30%. The results showed that the interaction between the concentration of stabilizer with the concentration of yoghurt had highly significant effect (P<0,01) on organoleptic value of texture and had significant effect (P<0,05) on moisture content and ash content. The best quality of belimbing wuluh jelly candy based on sensory characteristic and moisture content was the treatment with the concentration of stabilizer of 6% (A3) and the concentration of yoghurt of 30% (Y3). Value of texture analysis of the best quality of belimbing wuluh jelly candy were: hardness 2,1662 kgf, cohesiveness 0,394 gf; elasticity 65,564% respectively. Keywords : Belimbing Wuluh, Jelly Candy, Stabilizer, Yoghurt